Leaching of Ni-Cu-Fe-S Peirce Smith converter matte : effects of the Fe-endpoint and leaching conditions on kinetics and mineralogy. - Van Schalkwyk, R. F. (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScEng)--Stellenbosch University, 2011.